CLASSIFICATION OF MANTLE PERIDOTITES ON THE BASIS OF THE COMPOSITION OF THEIR ACCESSORY CHROME SPINELS - Palandzhyan S.A.; Dmitrenko G.G. (My University, 1989)
The authors classified mantle peridotites in terms of the chemical composition of accessory chrome spinels only from harzburgites and 1herzolites containing no plagioclase. The sample of about 370 analyses includes data on rocks from the present ocean floor, the marginal seas, alpinotype peridotites of the folded rim of the Pacific Ocean, the Urals, Soviet Central Asia, the Mediterranean region, and deep-seated inclusions in alkalic basalts of the Soviet Far Eastern Maritime Province. Most data were taken from published sources, but microprobe analyses of the accessory chrome spinels in 75 samples of alpinotype peridotite from the Koryak Highlands were especially done for this investigation. The compositions of all accessory spinels used in this work are typical of chrome spinels of metamorphic peridotites. The variations observed in the main components are caused by very intensive Al-Cr replacement, in parallel with moderate Mg-Fe 2+ replacement, the content of ferric iron being then very low. Given this chemistry of the chrome spinels, one can classify the peridotites on the basis of the distribution of a single index, namely the chromian index of their spinels Cr/(Cr+Al).